Penyajian Data Hidrologi Tersebar di Sulawesi Selatan dengan Menggunakan Sistem Informasi Geografis (SIG) - Faisal, Zulvyah; Iqbal, Muhammad Taufik (INTEK: Jurnal Penelitian, 2017)
Hydrological data is the data that became the basis of planning activities Water Resources Management (SDA) in the river area, such as irrigation building planning, water building, river management, flood control and others. Therefore, hydrological data needs to be managed into a geographic information system to provide accurate, true and timely SDA information for all interested parties. By knowing the position of climate observation post and rain station along with the climatic and rainy data, which can be observed by the public, it is expected that the control over the implementation of development can be done more openly. The results obtained from this research are digital map position of observation post along with climate data, water level and rainfall along with South Sulawesi Province that can be used by public, government, and educational institution that need location of station position and data recording climate observations, water levels and rainfall in South Sulawesi.